EVALUASI PENYIMPANAN OBAT DI APOTEK INDRA SUKOHARJO - Dwi H, Aminah; Hartono (Jurnal Farmasi (Journal of Pharmacy), 2023)
Regulation of the Minister of Health of the Republic of Indonesia No. 73 of 2016 concerning Pharmacy Pharmaceutical Service Standards states that pharmacies are a means of pharmaceutical services where pharmaceutical practices are carried out by Pharmacists. Pharmaceutical service standards that aim to improve the quality of pharmaceutical services, security, storage and distribution or distribution of drugs, services on prescriptions or not with prescriptions, drug information services, guarantee legal certainty for pharmaceutical personnel, and protect patients and the public from irrational use of drugs in the context of patient safety. Good drug storage will ensure the quality of drug preparations, avoid irresponsible use of drugs, maintain the availability and service of pharmaceuticals and facilitate the search and supervision. Evaluation of good drug storage should be carried out by all pharmaceutical services including pharmacies. This study aims to evaluate drug storage in Indra pharmacies based on the physical condition of drug storage shelves and warehouses, how to store drugs, record stock cards, and safeguard drug quality. This research is a type of observational research by observing objects and the results are presented descriptively, and data collection is carried out by documentation and interviews at the Pharmacist in Charge of Apotek Indra Sukoharjo. The results of the evaluation of drug storage at Indra Sukoharjo Pharmacy as many as 77.8% have met the standards in accordance with the Regulation of the Minister of Health Number 73 of 2016 concerning Pharmaceutical Service Standards in Pharmacies. The results of the evaluation of the condition of the rooms and facilities in the drug storage warehouse of Apotek Indra Sukoharjo based on the Technical Guidelines for Good Drug Distribution Methods set by the Food and Drug Control Agency in 2020 were 54.2% who had met the standards and 45.8% had not met the standards.